Climate change, public health, and animal welfare: towards a One Health approach to reducing animal agriculture’s climate footprint - Verkuijl, Cleo; Smit, Jessie; Green, Jonathan M. H.; Nordquist, Rebecca E.; Sebo, Jeff; Hayek, Matthew N.; Hötzel, Maria José (Frontiers in Animal Science, 2024)
Animal agriculture contributes significantly to global greenhouse gas (GHG) emissions—an estimated 12%-20% of total anthropogenic emissions. This has led both governmental and private actors to propose various ways to mitigate those climate impacts. This paper applies a One Health lens to the issue, arguing that the choice of solutions should not only consider the potential to reduce GHG emissions—which is not always a given—but also the implications for public health and animal welfare. With this perspective, we examine the potential public health and animal welfare impacts of three types of strategies that are often proposed: (1) “sustainable intensification” methods, aimed at maintaining or increasing production while limiting emissions and avoiding further land conversion; (2) “species shift” approaches, which focus on changing diets to consume meat from animals produced with lower GHG emissions instead of that of animals associated with higher emissions; and (3) “systemic dietary change” approaches that promote shifts towards plant-based or lab-grown alternatives to animal products. We discuss how some approaches—particularly those associated with sustainable intensification and species shift—could introduce new and significant risks to public health and animal welfare. Promoting systemic dietary change is less risky in that regard, but requires careful attention to equity, to ensure that vulnerable populations still have access to the nutrients they need. We end with recommendations for a more holistic approach to reducing emissions from farmed animals that can help avoid trade-offs and increase synergies with other societal goals.